ANALISIS PENGARUH OPERATING LEVERAGE DAN FINANCIAL LEVERAGE TERHADAP PROFITABILITAS (Studi Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Putra, Yoga Rachmawan (Jurnal Ilmiah Mahasiswa FEB, 2017)
The purpose of  this  study  is  to  determine  whether  operating  leverage  and  financial leverage have any impact toward profitability. This study was conducted on banking companies listed in the Indonesia Stock Exchange from 2013 to 2015. From the population of 30 banking companies, ten of them were selected as the sample. The data were analysed using multiple linear regression analysis. The result of this study reveals that degree of operating  leverage  and  degree  of financial leverage  simultaneously  influence  return  on equity significantly (0,001 < 0,05). Partially, degree of operating leverage has a negative and significant impact on return on equity (0,001 < 0,05), and degree of financial leverage does not have any significant impact on return on equity (0,061 > 0,05).Key Word: capital, profitability, operating leverage, financial leverage, return on equity.